Pola Pembinaan Santri dalam Pengendalian Perilaku Menyimpang di Pondok Pesantren ar-Risalah Kota Jember - Suryadi Suryadi; Maslahatun Nikmah (Institut Agama Islam Negeri (IAIN) Curup, 2019)
This article discusses the pattern of fostering deviant behavior that occurs among students. This research took place in Islamic boarding school to become one of the institutions of education that is fairly old in the Indonesian nation. In addition, Islamic boarding schools are also known as institutions to deepen knowledge and foster student morals. Therefore, each boarding school has a different pattern of coaching. This study uses field research (field research) with a descriptive qualitative approach. The aim is to be able to describe the results of the analysis in detail. This problem attracts the attention of the writer to examine the pattern of guidance of students in controlling deviant behavior. Based on the results of the study it can be seen that the factors causing deviant behavior of students are influenced by the family environment, boarding schools/schools and peers. As for the pattern of fostering santri in controlling deviant behavior in the boarding school of ar-Risalah, the village uses three coaching patterns, namely a preventive pattern, a repressive pattern and a curative pattern. Patterns of prevention are carried out to keep the delinquency from happening. Repressive patterns when students have deviant behavior so there must be consequences for the students. And curative control pattern is given if the pattern of preventive and repressive can not be a solution in controlling deviant behavior of students.